2015
DOI: 10.1186/s40425-015-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-adjuvanted mRNA vaccination in advanced prostate cancer patients: a first-in-man phase I/IIa study

Abstract: BackgroundCV9103 is a prostate-cancer vaccine containing self-adjuvanted mRNA (RNActive®) encoding the antigens PSA, PSCA, PSMA, and STEAP1. This phase I/IIa study evaluated safety and immunogenicity of CV9103 in patients with advanced castration-resistant prostate-cancer.Methods44 Patients received up to 5 intra-dermal vaccinations. Three dose levels of total mRNA were tested in Phase I in cohorts of 3–6 patients to determine a recommended dose. In phase II, 32 additional patients were treated at the recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(167 citation statements)
references
References 48 publications
(52 reference statements)
1
155
0
3
Order By: Relevance
“…Active cancer immunotherapy based on CureVac's mRNA technology was previously shown to be safe and well tolerated and potently induced vaccine antigen-specific immune responses 26 . Similar observations were made in the clinical trial of CV9201 in NSCLC described here (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Active cancer immunotherapy based on CureVac's mRNA technology was previously shown to be safe and well tolerated and potently induced vaccine antigen-specific immune responses 26 . Similar observations were made in the clinical trial of CV9201 in NSCLC described here (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 78%
“…This study showed that repeated immunizations with two-component mRNA vaccines, encoding prostate cancer-associated antigens, induced vaccine-specific immune responses and were well tolerated showing a favorable safety profile 26 . We have also successfully completed a phase I/IIa trial, conducted in patients with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 83%
“…One such study demonstrated that mRNAs encoding survivin and various melanoma tumour antigens resulted in increased numbers of antigen-specific T cells in a subset of patients with melanoma 150 . In humans with castration-resistant prostate cancer, an RNActive vaccine expressing multiple prostate cancer-associated proteins elicited antigen-specific T cell responses in the majority of recipients 151 . Lipid-based carriers have also contributed to the efficacy of intra-dermally delivered mRNA cancer vaccines.…”
Section: Mrna Cancer Vaccinesmentioning
confidence: 99%
“…Nonetheless, there have been encouraging preliminary results of recent and ongoing clinical trials using mRNA, underscoring the rapidly emerging importance of mRNA therapeutics in the treatment or prevention of a range of diseases. To date, naked, chemically modified, or protamine-complexed mRNA have shown promise in phase I/II cancer trials (24)(25)(26). Recently, preclinical development of materials specific for mRNA delivery has resulted in cationic polymers such as polymethacrylates (27)(28)(29), poly(aspartamides) (30,31), and polypeptides (32), as well as multicomponent cationic lipid or lipid-like formulations (21,(33)(34)(35)(36).…”
mentioning
confidence: 99%